Newcastle Disease Virus-Specific RNA: Polyacrylamide Gel Analysis of Single-Stranded RNA and Hybrid Duplexes - Kaverin, Nicolai V. (1974)
Newcastle disease virus-specific [(3)H]uridine-labeled 18S RNA was resolved by polyacrylamide gel electrophoresis into several components with molecular weights from 450,000 to 840,000. The analysis of 35 and 24S virus-specific RNA also revealed several components in each sedimentational class. The conversion of 18S RNA into double-stranded form by hybridization with an excess of unlabeled virion RNA improved the resolution in polyacrylamide gels and revealed at least six distinct components. The same six classes of hybrid duplexes were revealed when (32)P-labeled 50S virion RNA was hybridized with an excess of 18S RNA. The applicability of polyacrylamide gel electrophoresis of hybrid duplexes to the analysis of viral genome structure is discussed.